Workforce in the pharmaceutical services of the primary health care of SUS, Brazil - Carvalho, Marselle Nobre; Álvares, Juliana; Costa, Karen Sarmento; Guerra Junior, Augusto Afonso; Acurcio, Francisco de Assis; Costa, Ediná Alves; Guibu, Ione Aquemi; Soeiro, Orlando Mario; Karnikowski, Margô Gomes de Oliveira; Leite, Silvana Nair (Revista de Saúde Pública, 2017)
OBJECTIVE: To characterize the workforce in the pharmaceutical services in the primary care of the Brazilian Unified Health System (SUS). METHODS: This is a cross-sectional and quantitative study, with data from the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Serviços, 2015 (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines – Services, 2015). For the analysis, we considered the data stratification into geographical regions. We analyzed the data on workers in the municipal pharmaceutical services management and in the medicine dispensing units, according to the country’s regions. For the statistical association analysis, we carried out a Pearson correlation test for the categorical variables. RESULTS: We analyzed 1,175 pharmacies/dispensing units, 507 phone interviews (495 pharmaceutical services coordinators), and 1,139 professionals responsible for medicine delivery. The workforce in pharmaceutical services was mostly constituted by women, aged from 18 to 39 years, with higher education (90.7% in coordination and 45.5% in dispensing units), having permanent employment bonds (public tender), being for more than one year in the position or duty, and with weekly work hours above 30h, working both in municipal management and in medicine dispensing units. We observed regional differences in the workforce composition in dispensing units, with higher percentage of pharmacists in the Southeast and Midwest regions. CONCLUSIONS: The professionalization of municipal management posts in primary health care is an achievement in the organization of the workforce in pharmaceutical services. However, significant deficiencies exist in the workforce composition in medicine dispensing units, which may compromise the medicine use quality and its results in population health